PENYELESAIAN SENGKETA LINGKUNGAN HIDUP DI LUAR PENGADILAN - Elvie Wahyuni (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2009)
Environmental law enforcement must not be always through thejustice institution but it also can be done outside of it that iscaused by exploitation activity of natural resource ignorednatural and environmental conservation. Therefore, win-winsolution is one of ways that can be done that nobody harmedand the agreement will give more justice. The effort in finishingthe lawsuit of living environment outside the court should bedone voluntarily by people involved, those who stand the loss,cause the loss and also the governmental institutions related tothe subject who have the lawsuit. It can also involve those whoconcern to living environment.